Breathless [compact disc, unabridged] : a novel - Koontz, Dean R. (Dean Ray), 1945- (Brilliance Audio, 2009)
Grady Adams lives a simple, solitary life deep in the Colorado mountains. Here the thirty-five-year-old carpenter works out of a converted barn, crafting exquisite one-of-a-kind furniture. There's little about this strong yet gentle man to suggest the experiences that have alienated him from the contemporary world. But that is about to change.